PENGARUH MODEL PROBLEM BASED LEARNING (PBL) MENGGUNAKAN METODE PRAKTIKUM TERHADAP AKTIVITAS DAN HASIL BELAJAR SISWA - Nopianti, Rahayu; Toto, Toto (Universitas Galuh, 2019)
The aim of this study is to determine the effect of the Problem Based Learning model through practicum on student activities and learning outcomes. This research method is Quasi Experimental Design method. The study population was three classes at a MAN in Cimis. The research sample is one class X MIA1 of 33 students. The sampling technique uses purposive sampling. The research instrument used was the observation score and multiple choice questions. Data analysis using Wilcoxon and z test. The results of the study concluded that the application of the model of problem based learning (PBL) through practicum affects the activities and student learning outcomesKeywords: Problem Based Learning using practicum methods, activities, learningÂ outcomes